PTU-055 The association of co-existent non-ischaemic cardiac disease with morbidity and mortality following liver transplantation. (28th May 2012) - Steed, H; Leithead, J A; Kandiah, K; Gunson, B K; Ferguson, J W
Abstract : Introduction: The risk stratification of potential liver transplant candidates with co-existent non-ischaemic cardiac disease (CD) is particularly challenging given the masking effect of the haemodynamic dysfunction of advanced portal hypertension. Whether such patients have altered outcomes following liver transplantation remains unknown. Our aim was, therefore, to examine the effects of mild and moderate non-ischaemic CD on post liver transplant morbidity and mortality. Methods: Single-centre study of patients undergoing first liver transplantation for chronic liver disease. To determine the effects of mild CD, the routine assessment trans-thoracic echocardiography reports of 246 patients transplanted 01/2007–03/2010 were reviewed. To determine the effects of moderate CD, patients transplanted from 1994-present were highlighted from a prospectively collected database. Results: Mild CD 11.4%, 11.4%, 2.8%, and 0.8% of the 246 patients undergoing routine assessment echocardiography had left atrial dilatation, or mild mitral regurgitation, aortic regurgitation or aortic stenosis, respectively. After adjusting for confounding variables there was no association between left atrial dilatation (p=0.738) or mild mitral regurgitation (p=0.234) and a cardiac event post transplant. Similarly, there was no association between left atrial dilatation (p=0.146) or mild mitral regurgitation (p=0.157) and post transplant survival. Moderate CD Ten patients were transplanted with moderate CD: aortic valve replacement (4), moderate valvular dysfunction (2), HOCM (2), moderate left ventricular failure (1), mitral valvuloplasty (1). Two of these patients underwent simultaneous valve replacement surgery. Of these two patients, one had a peri-operative cardiac event and both were alive at 1-year. For the remaining eight patients who did not undergo intervention the cumulative incidence of a cardiac event by 1-year after transplantation was 68.7%, and the estimated 1-year survival was 46.7%. All three patients with a pre-existing aortic valve replacement that was not re-done had a cardiac complication: one patient developed bacterial endocarditis and awaits further valve replacement surgery, two died of cardiac failure at 90- and 200-days post transplant. Conclusion: Chronic liver disease patients with co-existent moderate CD who receive a favourable cardiac risk assessment have greater than expected morbidity and mortality following liver transplantation. Our findings suggest that the severity of non-ischaemic CD is underestimated in this setting. Competing interests: None declared.